Síndrome da fragilidade e complexidade do controle postural baseado na análise de entropia - Carmelo, Verena de Vassimon Barroso (Universidade Federal de São Carlos, 2015)
Frailty Syndrome represents a clinical state of vulnerability, resulting from decline of resilience and physiological reserves and it is associated with adverse outcomes such as falls. Thus, the aim of this study was to evaluate the complexity of oscillations of center of pressure (CoP)in the frailty syndrome before and after a functional task. CoP oscillations in the anteroposterior (AP) and mediolateral (ML) direction was obtained by a force platform in a quite-standing position, 30 seconds before and after standing from a chair. Additionally, it was performed the timed up and Go test (TUGT). The complexity of CoP oscillations was analyzed by entropies: corrected approximate (CApEn), sample (SampEn) and conditional (CI), as well as their normalized versions (NCApEn, NSampEn and NCI). Linear data of CoP oscillations were obtained by amplitude, RMS and the total average speed (TAS). Repeated measures two way analysis of variance was carried out to evaluate the effects of groups, time (pre and post-functional task) and the interaction between them for complexity variables. Forty-two elderly were evaluated, divided into groups: nonfrail (n = 15; 75.6± 4.2 years), prefrail (n = 15; 78.9± 6.8 years) and frail (n = 12; 73.0±19.2 years). In the AP direction, only nonfrail and pre-frail elderly subjects showed significant reduction after functional task in CApEn, NCApEn, SampEn, NSampEn and NCI and significant increase in RMS. In the ML direction, only nonfrail showed significant reduction in complexity after functional activity in CApEn, NCApEn, SampEn and NSampEn. All groups showed significant increase in the RMS after the functional activity in the ML direction. A significant correlation was observed between the performance on the TUGT and the complexity indices (CApEn and NCApEn) in post- functional task only for nonfrail subjects in the AP direction. Then, after a voluntary disturbance on balance, frail elderly subjects show no variation in CoP oscillations entropy indexes suggesting a deficit in the postural control, possibly because the basal values are already reduced.
Keywords: Envelhecimento; Fragilidade; Complexidade; Entropia; Controle postural; Aging; Frailty; Complexity; Entropy; Postural control; Balance; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL